A novel tRNA-derived fragment, tRF-19-79MP9PJZ, promotes uterine corpus endometrial carcinoma progression by targeting DSC3 - Huabo Jiang; Ting Jiang; Yuting Shen; Hongyan Jiang; Qing Yuan (Human Cell, 2026)
Uterine corpus endometrial carcinoma (UCEC) ranks as the 6th most common malignancy among women. Emerging evidence indicates that the dysregulation of tRNA-derived fragments (tRFs) is involved in the pathogenesis of multiple cancer types, including UCEC; however, the molecular mechanisms underlying the roles of tRFs in UCEC remain poorly characterized. Desmocollin3 (DSC3), a transmembrane protein, is predominantly expressed in the basal and suprabasal layers of normal stratified epithelia. While accumulating evidence has implicated DSC3 in the pathogenesis of multiple disease entities, its functional role in UCEC remains elusive. The present study is designed to investigate the functional significance and underlying molecular mechanisms of tRF-19-79MP9PJZ in the progression of UCEC. In this study, tRF-19-79MP9PJZ was found to be significantly upregulated in UCEC tissues and cell lines, with its elevated expression correlating with unfavorable prognostic outcomes in UCEC patients. Furthermore, tRF-19-79MP9PJZ knockdown was observed to suppress the proliferative and migratory capacities of UCEC cells, while concurrently enhancing apoptotic processes. At the mechanistic level, tRF-19-79MP9PJZ was demonstrated to facilitate UCEC progression through targeted regulation of DSC3. Collectively, this study elucidates a previously uncharacterized mechanism whereby tRF-19-79MP9PJZ drives UCEC development, thereby highlighting the potential of the tRF-19-79MP9PJZ/DSC3 axis as a therapeutic target for UCEC intervention.